Concentration of Heavy Metals Pb and Cu in some parts of Mudskipper (Periophthalmus sp) in The Strait Waters of Rupat, Riau Province - Wage Pranowo; Syahril Nedi; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Heavy metals pollution has become problem in coastal waters due to anthropogenic activities such as disposal of industrial waste, sailing and mining. The research of heavy metals concentration Pb and Cu on mudskipper’s organ systems (muscles, gills and bones) was conducted. It is found that the content of Pb in muscles, gills and bones is in the range 4,6563 – 5,4231 (μg/g), 3,0857 – 4,1851(μg/g), and 2,7716 – 4,1205 (μg/g). While the content of Cu in the muscles, gills and bones is in the range 3,0317 – 3,3333 (μg/g), 1,7619 – 2,8810 (μg/g), and 1,9762 – 3,0159 (μg/g). There is a clear difference on the concentratin of Pb and Cu in muscles, gills an bones (P<0,01). Based on the accumulation of the heavy metals concentration in Mudskipper, the content of Pb and Cu is higher in the small size of Mudskipper than in the big size of Mudskipper. According to the sampling location, the highest Pb composition found in North Rupat Waters, 4,3838(μg/g) while the highest Cu composition found in Dumai Coastal Waters, 2,6085(μg/g).Keywords : Heavy Metals , Mudskipper (Periophthalmus sp), Rupat Strait